Microcrédito e inserção social em cidades baianas: estudo da experiência do Centro de Apoio aos Pequenos Empreendimentos da Bahia - CEAPE/BAHIA - Corsini, José Nélio Monteiro (2007)
A study developed from the inquiry of an experience put into effect by the Ceape/Bahia, identifies the relation between microcredit and social insertion in Bahia s cities. The theoretical basis of the study rely on what is called "economy of the poverty and microcredit": the upper and lower circuits of the economy, understanding the small enterprises of the urban informal economy, as a result of the urbanization and the productive reorganization of the Brazilian economy in the last decades, detaching the financing of the economic initiatives of small dimension in the perspective of the social insertion of entrepreneurs. The methodology that guided the research lead to the obedience of the following steps: first, the understanding of the terminology that leads to social insertion, as well as to the collection and treatment of information of Ceape`s data-base. Afterwards, it was carried out a field research when a representative sample of costumers were interviewed to search the perception of the microcredit beneficiaries. With the recital propitiated for a panoramic vision of the experiences of microcredit in Brazil and the world, the study concentrates in the case of the Ceape/Bahia, presenting a historical briefing of the organization, the institucional structure and the geographic area of the attendance. It studies the characteristics of customers, the financed enterprises and the granted operations of microcredit in the investigated period. The analysis of the data gotten in the field research focuses the impact of the microcredit on the material condition of life and sociability of the customers, in search of evidences to answer to the problem, the hypothesis and the objectives of the inquiry, in the perspective of the social insertion of the beneficiary people. The research verified evidences of the contribution of the microcredit in the social insertion of the entrepreneurs in result of the application of the resources in the financed productive activities, repercuting in diverse aspects of the material conditions of life and the sociability of the customers.